Design, modeling and implementation of antennas using electromagnetic bandgap material and defected ground planes - Zainal Abidin, Zuhairah (2011)
The main objective of this research is to design, model and implement several antenna geometries using electromagnetic band gap (EBG) material and a defected ground plane. Several antenna applications are addressed with the aim of improving performance, particularly the mutual coupling between the elements. The EBG structures have the unique capability to prevent or assist the propagation of electromagnetic waves in a specific band of frequencies, and have been incorporated here in antenna structures to improve patterns and reduce mutual coupling in multielement arrays. A neutralization technique and defected ground plane structures have also been investigated as alternative approaches, and may be more practical in real applications. A new Uni-planar Compact EBG (UC-EBG) formed from a compact unit cell was presented, giving a stop band in the 2.4 GHz WLAN range. Dual band forms of the neutralization and defected ground plane techniques have also been developed and measured. The recorded results for all antenna configurations show good improvement in terms of the mutual coupling effect. The MIMO antenna performance with EBG neutralization and defected ground of several wireless communication applications were analysed and evaluated. The correlation coefficient, total active reflection coefficient (TARC), channel capacity and capacity loss of the array antenna were computed and the results compared to measurements with good agreement. In addition, a computational method combining Genetic Algorithm (GA) with surface meshing code for the analysis of a 2x2 antenna arrays on EBG was developed. Here the impedance matrix resulting from the meshing analysis is manipulated by the GA process in order to find the optimal antenna and EBG operated at 2.4 GHz with the goal of targeting a specific fitness function. Furthermore, an investigation of GA on 2x2 printed slot on DGS was also done.